Comparison of homopolar and heteropolar bearingless reluctance slice motor prototypes. (May 2017) - Gruber, Wolfgang; Bauer, Walter; Radman, Karlo
This article focuses on the operational behaviours of two novel bearingless reluctance slice motor prototypes. After a brief introduction of the two systems, we present our experience with both bearingless drives. On this basis, commonalities and differences in terms of construction, geometric constraints, winding systems, force-to-torque ratio, power electronic utilization and efficiency are outlined in order to demonstrate the suitability of the reluctance slice motor concepts for industrial applications.